Manajemen Konflik dalam Perspektif Tahapan dan Resolusi: Temuan Sintesis dari Literature Review Sistematis - Andini Setia Winata; Efan Andika Putra; Eka Khoirena Firdausy; Ananda Syaiba Suri Kholafi; Mu’alimin Mu’alimin (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
Conflict is an inevitable phenomenon in organizations and educational institutions, and if not managed properly can have a negative impact on performance, effectiveness, and interpersonal relationships. However, conflict also has the potential to be a catalyst for improvement if managed appropriately. Therefore, it is important to systematically examine the stages of conflict, their impacts, and relevant management strategies. This study aims to answer the following questions: (1) How are the stages of conflict identified in various organizational and educational contexts? (2) What are the impacts of conflict on organizations? and (3) What management strategies are most effectively implemented? The method used was a literature review by searching articles through national and international databases using the keywords stages of conflict, conflict management, and education. Of the 73 initial articles, 18 primary articles were selected for thematic analysis. The analysis revealed three main findings: (1) conflict generally develops through stages of latency, escalation, and overt manifestation; (2) conflict negatively impacts performance if left unchecked, but can be constructive if managed; and (3) effective conflict management strategies are contextual, combining structural, interpersonal, and cultural-religious value approaches. In conclusion, this literature highlights the need for adaptive conflict management to maintain organizational stability. Further research is suggested to explore integrative models of conflict management based on local values and educational practices.